Costs and Economic Impacts of Physician Continuous Professional Development: A Systematic Scoping Review. (28th December 2021) - Cook, David A.; Stephenson, Christopher R.; Wilkinson, John M.; Maloney, Stephen; Baasch Thomas, Barbara L.; Prokop, Larry J.; Foo, Jonathan
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: Nearly all health care professionals engage in continuous professional development (CPD), yet little is known about the cost and cost-effectiveness of physician CPD. Clarification of key concepts, comprehensive identification of published work, and determination of research gaps would facilitate application of existing evidence and planning for future investigations. The authors sought to systematically map study themes, methods, and outcomes in peer-reviewed literature on the cost and value of physician CPD. Method: The authors conducted a scoping review, systematically searching MEDLINE, Embase, PsycInfo, and Cochrane Library databases for comparative economic evaluations of CPD for practicing physicians through April 2020. Two reviewers, working independently, screened all articles for inclusion. Three reviewers iteratively reviewed all included articles to inductively identify key features including participants, educational interventions, study designs, cost ingredients, and cost analyses. Two reviewers then independently reexamined all included articles to code these features. Results: Of 3, 338 potentially eligible studies, 111 were included. Physician specialties included internal, family, or general medicine (80 studies [72%]), surgery (14 studies [13%]), and medicine subspecialties (7 studies [6%]). Topics most often addressed general medicine (45 studies [41%]) or appropriate drug use (37 studies [33%]). Eighty-seven studies (78%) compared CPD with no intervention. Sixty-three studies (57%) reported the cost of training, and 79 (71%) evaluated the economic impact (money saved/lost following CPD). Training cost ingredients (median 3 itemized per study) and economic impact ingredients (median 1 per study) were infrequently and incompletely identified, quantified, or priced. Twenty-seven studies (24%) reported cost–impact expressions such as cost-effectiveness ratio or net value. Nineteen studies (17%) reported sensitivity analyses. Conclusions: Studies evaluating the costs and economic impact of physician CPD are few. Gaps exist in identification, quantification, pricing, and analysis of cost outcomes. The authors propose a comprehensive framework for appraising ingredients and a preliminary reference case for economic evaluations.